Amorphous Conjugated Polymers as Efficient Dual‐Mode MALDI Matrices for Low‐Molecular‐Weight Analytes. Issue 9 (10th July 2019) - Horatz, Kilian; Ditte, Kristina; Prenveille, Thomas; Zhang, Ke‐Nan; Jehnichen, Dieter; Kiriy, Anton; Voit, Brigitte; Lissel, Franziska
Abstract: Matrix‐assisted laser desorption/ionization mass spectrometry (MALDI MS) usually employs highly crystalline small‐molecule matrices, and the analyte is interpreted as being co‐crystallized with the matrix. We recently showed that semi‐crystalline polymers are efficient matrices for the detection of low‐molecular‐weight compounds (LMWCs) in MALDI MS and MALDI MS Imaging, and are dual‐mode, i. e., enabling both positive and negative modes. The matrix performances of two fluorene/napthalene diimide co‐polymers P(TNDIT‐Fl(C4 C2 )) and P(TNDIT‐Fl(C10 C8 )) were investigated and compared. Both are fully amorphous according to XRD measurements, show high relative absorption values at the wavelength of common MALDI lasers (λNd:YAG =355 nm: C4 C2 =73 %; C10 C8 =67 %), and are solution processable. As matrices, they are dual‐mode, and enable the detection of LMWCs while being mostly MALDI‐silent. Compared with semicrystalline polymer matrices, the amorphous matrices give similar or better signal intensities, thus indicating that analyte inclusion takes place in the amorphous part of the polymer matrix. Abstract : The answer is out there : The matrix is crucial for MALDI measurements and good organic matrices are usually highly crystalline. Two amorphous co‐polymers P(TNDIT‐Fl(C4 C2 )) and P(TNDIT‐Fl(C10 C8 )) were investigated regarding their suitability as MALDI matrices for the analysis of single and complex low‐molecular‐weight compounds. Both co‐polymers show excellent performance as dual‐mode MALDI matrices, suggesting that analyte incorporation takes place in the amorphous phase.